.Mac with iWeb, Second Edition : Visual QuickStart Guide - Reynolds, David (Peachpit Press, 2006)
Need to learn what's new in .Mac fast? Try a Visual QuickStart! This best-selling reference's visual format and step-by-step, task-based instructions will have you up and running with .Mac in no time. In this completely updated edition of our best-selling guide to .Mac leading software application expert David Reynolds uses crystal-clear instructions and friendly prose to introduce you everything that's new. Filled with step-by-step, task-based instructions and loads of visual aids, this book explains how to publish your photos, movies, podcasts and blogs on the internet with iWeb; share your photo albums in iPhoto as a photocast; access your files from anywhere with iDisk; keep all your Macs in sync with another with .Mac sync; and more!